Peculiarities of water elemental composition at water use objects located at the territory of the former semipalatinsk test site - Gani Mukhtarovich Yessilkanov; Sergey Nikolaevich Lukashenko; Leonid Petrovich Rikhvanov; Madina Talgatovna Koygeldinova; Nurlan Zhumagazyevich Mukhamediyarov; Erbol Zeilgazinovich Shakenov; Aray Ermekovna Temirzhanova; Yuliya Yurievna Yakovenko (Известия Томского политехнического университета: Инжиниринг георесурсов, 2017)
Relevance of the work is determined by the necessity of obtaining reliable data on concentrations of chemical elements in water of the former Semipalatinsk test site water objects. This information is needed to reveal potentially-hazardous objects, those can affect the health of people inhabiting this territory. The aim of the work is to study the peculiarities of water ultimate composition in the water objects used by the people living at the territory of the former Semipalatinsk test site. The methods. Water ultimate composition was determined by inductively coupled plasma mass-spectrometry (Elan 9000 "Perkin Elmer SCIEX"), inductively coupled plasma atomic emission spectrometry ("iCAP 6300 Duo" Thermo Scientific). To analyze such characteristics as total salt content, content of sulphates, hydrocarbonates, chlorides, calcium, magnesium and sodium, the titrimetric, colorimetric, and potentiometric methods of measurement were used. Results. Chemical composition of water of the former Semipalatinsk test site water object is not uniform. 26 % of all the samples studied have hydrocarbonate-sodium-magnesium composition, 58 % - sulphate-sodium-magnesium, sulphate-sodium-magnesium and sulphate-sodium-calcium composition, 15 % - chloride-sodium-magnesium composition. Comparing the macrocomponent composition of water with an average composition of ground water of hypergenesis zone and continental salification zone, it was found that hydrocarbonate water is similar in composition with hypergenesis water. The studied sulphate and chloride water types are similar in macrocomonent composition with water of continental salification zone. To find the peculiarities in the former Semipalatinsk test site water ultimate composition, the authors have built the descending series of exceedence of concentrations related to the mean composition of hypergenesis zone water and continental salification zone water: U15>Mo13>Sr10 (hypergenesis zone), Mo5>U5>Sr3 (continental salification zone). The decreasing series show that in the former Semipalatinsk test site ground water such elements as U, Mo, Sr can be typically found. In water of 51 % of all the researched water objects of the former Semipalatinsk test site, the increased concentrations of U from 1 to 8 MPC (MPCU=15 μg/l) were found. According to results of isotopic analysis, uranium in water can be of natural origin. Excessive concentrations of Sr in ground water can be explained by the presence of strontium hydrogeochemical area at the territory of Kazakhstan. Therefore, the discovered increased concentrations of molybdenum, uranium and strontium in water of the former Semipalatinsk test site water objects are associated with the natural and climatic peculiarities of the region.